Understanding Health Inequality, Disparity and Inequity in Africa: A Rapid Review of Concepts, Root Causes, and Strategic Solutions - Gabriel Ilerioluwa Oke; Olivier Sibomana (Public Health Challenges)
ABSTRACT Introduction Health inequality, disparity, and inequity are critical global health challenges, particularly in low‐ and middle‐income countries (LMICs). Africa's healthcare systems have been profoundly impacted by these issues for decades, leading to severe and far‐reaching consequences. This rapid review aims to explore the concepts of health inequality, disparity, and inequity in Africa, identify their root causes, and propose practical recommendations to address them. Methodology A comprehensive search was conducted across PubMed, Google Scholar, the Directory of Open Access Journals (DOAJ), and through manual searches on Google to identify literature on health inequalities, disparities, and inequities in Africa. Key terms, such as “Health inequality,” “Health disparity,” “Health inequity,” “Health injustice,” “Health unfairness,” “Healthcare access,” and “Health challenges,” were employed. The identified literature was carefully reviewed, and relevant sources were selected to discuss the concepts, causes, and potential solutions to these differences in health outcomes across Africa. Results Although some aspects of health inequality are linked to unmodifiable factors, health disparities and inequities are often the result of preventable and modifiable factors and can be addressed through targeted efforts. The root causes of health inequality, disparity, and inequity in Africa include poverty, inadequate education, corruption, poor governance, geographic isolation, unsupportive environmental conditions, cultural norms, and international influences. Solutions to these differences in health outcome lie in reversing the root causes. Conclusion Addressing health inequality, disparity, and inequity in Africa requires a multifaceted approach, including improving education, healthcare infrastructure, and gender equality, alleviating poverty, and ensuring fair governance to achieve equitable health outcomes.